The Correlation of Knowledge with Leucorrhea in Female Students of MTsN Batang Toru - Khairani, Fitri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
The worst health problems of female reproduction have reached 33% of the total burden of disease that affects women in the world. One of the symptoms of the occurrence of abnormalities or diseases of the reproductive organs is leucorrhea. Leucorrhea that affects is pathological leucorrhea caused by infection in the vagina. World Health Organization states that 5% of teens in the world contracted Sexually Transmitted Diseases with leucorrhea symptoms every year. There are several factors that affect the occurrence of leucorrhea in women, especially in adolescents, such as lack of adolescent knowledge about leucorrhea. This study aims to determine the correlation of knowledge with leucorrhea in female students of MTsN Batang Toru on 2017. The type of this research is analytic descriptive by using cross sectional approach. The population of this research were all of female students class of 7th and 8 th of MTsN Batang Toru South Tapanuli District as many as 259 respondents. Statistical tests performed using the Chi-square test with α = 0,05. The results of research by bivariate analysis shows that there was a relationship between knowledge and leucorrhea (p < 0,001). From the results obtained, it is advisable to female student of MTsN Batang Toru to find more information and read books about leucorrhea and its impact on reproductive health, especially for adolescents so that it can motivate themselves to know more about prevention.